Systems biology : properties of reconstructed networks - Palsson, Bernhard (Cambridge University Press, 2006)
The new discipline of sytems biology examines how genome sequences interact and form networks. This text describes how to model networks, how to determine their properties, and how to relate these to phenotypic functions. The prerequisites for this text are knowledge of linear algebra and biochemistry.